2010
DOI: 10.3109/0886022x.2010.510234
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of acute kidney injury in patients with traumatic brain injury

Abstract: There is limited information on the incidence of acute kidney injury (AKI) in patients with traumatic brain injury (TBI) although AKI may contribute to morbidity and mortality. We investigated the incidence of AKI in patients with moderate and severe TBI and the association of AKI with risk factors and outcomes in these patients. We studied all TBI patients over 16 years of age admitted to the two designated trauma hospitals in the state of Victoria, Australia from 1 January to 31 December 2008. Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 25 publications
5
68
0
Order By: Relevance
“…One possible explanation is that TBI, which is common in combat casualties, is modulating the effect. In a recent study, the incidence of AKI in the setting of TBI was 9.2% and was associated with a mortality rate of 42.1% compared with 18.1% in patients without AKI (25). Although TBI was not associated with mortality in our population, the low incidence (8.8% in the cohort with $20% TBSA) makes a significant difference difficult to detect.…”
Section: Discussionmentioning
confidence: 45%
“…One possible explanation is that TBI, which is common in combat casualties, is modulating the effect. In a recent study, the incidence of AKI in the setting of TBI was 9.2% and was associated with a mortality rate of 42.1% compared with 18.1% in patients without AKI (25). Although TBI was not associated with mortality in our population, the low incidence (8.8% in the cohort with $20% TBSA) makes a significant difference difficult to detect.…”
Section: Discussionmentioning
confidence: 45%
“…The natural follow-up question is to address whether this new system of renal dysfunction stratification carries any medical significance. Recently, Zacharia reported an incidence of AKI in 23% of patients with aneurysmal SAH [17], and Moore reported an incidence of AKI in 9% of TBI patients with GCS less than 13 [18]. Importantly, these AKI patients had an increased risk of MOF and death.…”
Section: Discussionmentioning
confidence: 94%
“…It should also be mentioned that AKI is relatively common in patients with traumatic brain injury (TBI), with an incidence of 9.2%. 35 Our study showed that prolonged donor stay in the ICU is associated with more severe damage of donor kidney, which affects the outcome of transplant.…”
Section: Discussionmentioning
confidence: 71%